2018
DOI: 10.1108/jima-12-2016-0097
|View full text |Cite
|
Sign up to set email alerts
|

The effect of entrepreneurial marketing on halal food SMEs performance

Abstract: Purpose Small and medium enterprises (SMEs) need to use specific marketing strategies and approaches due to their limited resources and capabilities. Entrepreneurial marketing (EM) is an alternative marketing management approach under the special conditions that describe SMEs. Therefore, the purpose of this paper is to investigate whether EM has a positive and significant effect on different aspects of performance of Iranian halal food SMEs. Design/methodology/approach A correlative descriptive research meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 70 publications
1
50
1
Order By: Relevance
“…The advantage is that the owner/manager is closer to the market and can identify opportunities directly (Kilenthong et al, 2015). Fard and Amiri (2018) state that EM affects SMEs' market and innovation performance. Franco et al (2014) argue that EM has an important role in business growth and sustainability.…”
Section: Entrepreneurial Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage is that the owner/manager is closer to the market and can identify opportunities directly (Kilenthong et al, 2015). Fard and Amiri (2018) state that EM affects SMEs' market and innovation performance. Franco et al (2014) argue that EM has an important role in business growth and sustainability.…”
Section: Entrepreneurial Marketingmentioning
confidence: 99%
“…Studies exploring EM were conducted by previous researchers (Miles et al, 2015;Morrish, 2011;Stokes, 2000), while several other scholars used EM as an independent variable in growth and performance. Previous studies empirically shown that EM positively predicts performance (Becherer et al, 2012;Eggers et al, 2020;Fard & Amiri, 2018;Hamali, 2015;Sadiku-Dushi et al, 2019). Researchers discussed the predictors of EM, such as environmental and organisational influences (Morris et al, 2002), while others studied EM in a strategic context (Sullivan Mort et al, 2012) and in relation to firm capabilities (Whalen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Resource leveraging focuses on the effective utilisation of available resources and the discovery of new sources of resources. Value creation focuses on providing continuous value to customers (Becherer et al, 2012;Fard and Amiri, 2018). Lebans and Euske (2006) define firm performance as a set of financial and non-financial indicators that provide information on the accomplishment of objectives and results.…”
Section: Entrepreneurial Marketingmentioning
confidence: 99%
“…Conventional marketing theories applicable to large firms may not be applicable to SMEs. The limitations of resources and few customers suggest that entrepreneurial marketing becomes more suitable for SMEs (Franco et al, 2014;Fard and Amiri, 2018). Entrepreneurial marketing (EM) is a new paradigm that merges the principles of entrepreneurship and marketing together and describes the marketing processes of firms that pursue opportunities with limited resources in uncertain market conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Many aspects of private and public life must be changed online (Liguori and Winkler, 2020). Limited resources and few customers suggest that entrepreneurial marketing is more suitable for SMEs (Franco et al, 2014;Hendijani, Fard, and Seyyed Amiri, 2018). Entrepreneurial marketing is a very appropriate concept for SMEs to be used, and it is by such business having characteristics of straightforward unplanned business management and unclear division of tasks within the organization.…”
Section: Introductionmentioning
confidence: 99%